The CALorimetric Electron Telescope (CALET) for high-energy astroparticle physics on the International Space Station. (July 2015) - Adriani, O; Akaike, Y; Asano, K; Asaoka, Y; Bagliesi, M G; Bigongiari, G; Binns, W R; Bonechi, S; Bongi, M; Buckley, J H; Castellini, G; Cherry, M L; et al.
Abstract: The CALorimetric Electron Telescope (CALET) is a space experiment, currently under development by Japan in collaboration with Italy and the United States, which will measure the flux of cosmic-ray electrons (and positrons) up to 20 TeV energy, of gamma rays up to 10 TeV, of nuclei with Z from 1 to 40 up to 1 PeV energy, and will detect gamma-ray bursts in the 7 keV to 20 MeV energy range during a 5 year mission. These measurements are essential to investigate possible nearby astrophysical sources of high energy electrons, study the details of galactic particle propagation and search for dark matter signatures. The main detector of CALET, the Calorimeter, consists of a module to identify the particle charge, followed by a thin imaging calorimeter (3 radiation lengths) with tungsten plates interleaving scintillating fibre planes, and a thick energy measuring calorimeter (27 radiation lengths) composed of lead tungstate logs. The Calorimeter has the depth, imaging capabilities and energy resolution necessary for excellent separation between hadrons, electrons and gamma rays. The instrument is currently being prepared for launch (expected in 2015) to the International Space Station ISS, for installation on the Japanese Experiment Module - Exposure Facility (JEM-EF).